STRATEGI KARYAWAN DALAM MENINGKATKAN MINAT NASABAH MENABUNG DI BMT MASLAHAH CAPEM TEGALSIWALAN - Abd Ghafur; Iis Nurus Shobah (Faculty of Islamic Economics and Business, 2020)
Baitul Maal wa Tamwil (BMT) Maslahah Capem Tegalsiwalan which is a financial institution that implements a system based on Islamic sharia. In its application it does not use the principle of interest (Riba) but instead uses the principle of profit sharing (Nisbah) so as to guarantee the halal income. The goal of every company is to create satisfied customers. So we need the right service strategy to be able to provide satisfaction to customers and maintain customers. The purpose is to find out service to customer satisfaction, it can be known the cause of customer interest to save, namely the quality of BMT services Maslahah Capem Tegalsiwalan that satisfies customers, and it is known that the Sumberbulu community positively welcomed the presence of BMT Maslahah Capem Tegalsiwalan because the services provided by BMT employees Maslahah Capem Tegalsiwalan Tegalsiwalan is very good, public appreciation is more caused by the performance of BMT employees Maslahah Capem Tegalsiwalan who are all alumni of Islamic Boarding Schools, they show a positive attitude in serving customers. In addition, savings products provided by BMT Maslahah Capem Tegalsiwalan can be taken at any time if there is an urgent need, and there is a profit sharing every month. The procedure is quite easy, it is also the reason for customers to choose to save at BMT Maslahah Capem Tegalsiwalan.